Experimental determination of optimum cutting conditions in turning low alloyed steel with cemented carbide tool - Amin, A. K. M. Nurul; Sankar, Roy (1987)
A scientific method has been developed to determine the optimum values of machining variable, which does not involve costly and precision measuring instruments. On the basis of the existing theories and present experimental results the following have been established. Tool wear and cutting force are function of chip-tool contact process, which itself in turn is a function of cutting speed-V for given pair of work and tool materials and conditions of cut. At a definite value of V called critical cutting speed-Vc chip tool contact process and cutting force-P change abruptly. For determination of Vc curves of coefficient of chip shrinkage K vs. V may be used instead of the curves P vs. V. It has been also established that for single carbide tool material optimum value of cutting speed Vop is just below Vc ( Vop < Vc ). For double carbide tool material there exist two values of optimum cutting speed Vop and Vop where, Vop1 < Vc, and Vop2 a bit higher than Vc .